Design and implement of pulse width modulation with low-cost hardware in the loop - Qasim Al Azze; Mohammed Hasan Ali (International Journal of Power Electronics and Drive Systems (IJPEDS), 2020)
The paper presents a low-cost hardware in the loop based on Arduino. Sinusoidal Pulse Width Modulation (SPWM) designing, analyzing, and implementation is experimented as hardware in the loop. Sinusoidal Pulse Width Modulation implementation via MATLAB\Simulation demonstrates in this work. In this paper, Arduino Mega2560 platform, microcontroller, introduce as hardware. A comparative study of the both techniques is presented. Arduino interfaces with PC Target MATLAB environment. Three phases Voltage Source Inverter directs by the generated pulses that loads with three phases RLC. The obtaining output current and voltage waveform of RLC load of Hardware-in-the-Loop validates to the MATLAB\simulation output waveform. The compering shows the output waveforms are primarily having the same pattern. Arduino consider as the lost cost as microcontroller which could be used in real application.